2007
DOI: 10.1002/aic.11169
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prediction of adsorption equilibrium for a H2/N2/CH4/CO2 mixture

Abstract: mixture on activated carbon JX101 were collected by static and dynamic methods, respectively. The tested range covered temperatures of 283-328 K and pressures up to 30 Â 10 5 Pa. The difference in the adsorption mechanisms between the super-and sub-critical components was considered for both correlation of pure gas adsorption and prediction of multicomponent adsorption equilibrium. The surface heterogeneity, interaction among the adsorbed molecules, and the non-ideal behavior of the adsorbed phase were also ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…70 Among them, IAST (Ideal Adsorbed Solution Theory) 71 is a commonly used one in zeolites, 19,72,73 which can give good predictions of gas mixture adsorption, and it serves as the benchmark for the prediction of mixed-gas adsorption equilibria from single-component isotherms. [74][75][76] Encouraged by these works, several researchers have performed IAST calculations in MOFs to see if this is also applicable in this type of materials. For IRMOF-1, we found that the calculated adsorption selectivities with IAST are in good agreement with the GCMC simulations for CH 4 -H 2 , CO 2 -H 2 and CO 2 -CH 4 mixtures, 29 while for Cu-BTC, it agrees well with the GCMC simulations at low pressures, 29,77 except for CO 2 -H 2 29 as illustrated in Fig.…”
Section: Application Of Iast Methods To Mixture Separation In Mofsmentioning
confidence: 99%
“…70 Among them, IAST (Ideal Adsorbed Solution Theory) 71 is a commonly used one in zeolites, 19,72,73 which can give good predictions of gas mixture adsorption, and it serves as the benchmark for the prediction of mixed-gas adsorption equilibria from single-component isotherms. [74][75][76] Encouraged by these works, several researchers have performed IAST calculations in MOFs to see if this is also applicable in this type of materials. For IRMOF-1, we found that the calculated adsorption selectivities with IAST are in good agreement with the GCMC simulations for CH 4 -H 2 , CO 2 -H 2 and CO 2 -CH 4 mixtures, 29 while for Cu-BTC, it agrees well with the GCMC simulations at low pressures, 29,77 except for CO 2 -H 2 29 as illustrated in Fig.…”
Section: Application Of Iast Methods To Mixture Separation In Mofsmentioning
confidence: 99%
“…The separation coefficient can be evaluated either based on the adsorption isotherms of pure CH 4 and N 2 or based on breakthrough curves collected experimentally with gas mixtures. In the former case, a prediction model for multi component adsorption is used to determine the composition of equilibrium phases, and the relative prediction error can be less than 10 % (Wu et al 2007). In the latter case, helium is added to the mixture of CH 4 and N 2 serving as diluting gas because He was supposed not to adsorb on adsorbents.…”
Section: Evaluation Of Separation Coefficient Based On Experimentsmentioning
confidence: 99%
“…Other conditions necessary for the reliability of evaluation include keeping the adsorption bed isothermal, small pressure drop over the sorption bed and plug flow of gas stream. The calculation of separation coefficient based on breakthrough experiments was described in the literature (Yang 1987), and the reliability of evaluation was also previously proven (Wu et al 2007). …”
Section: Evaluation Of Separation Coefficient Based On Experimentsmentioning
confidence: 99%
“…13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28] Furthermore, it is commonly known that enhanced adsorption field in carbon nanopores increases CO 2 adsorption capacity and the equilibrium separation factor over mentioned above fluids at low pore loadings. [5][6][7][8][9][10]15,[29][30][31][32][33][34][35] However, it is not clear how various factors, including: bulk mixture composition, pore loading, the number and type of surface oxygen-containing groups, and carbon texture impact on the CO 2 /CH 4 separation factor near ambient operating conditions.…”
Section: Introductionmentioning
confidence: 99%